Distinctive functional characteristics of human "T" lymphocytes defined by E rosetting or a monoclonal anti-T cell antibody. - Beverley, P; Callard, R (1981)
The properties of human lymphocyte fractions isolated either by sheep red cell(E) rosetting or by fluorescence-activated cell sorting after staining with UCHT1 monoclonal anti-T cell antibody have been compared. Two populations of E+ cells with very different phenotype and function have been identified. E+/UCHT1+ cells respond well to the T cell mitogens phytohemagglutinin and concanavalin A and provide help for an in vitro specific antibody response. They can also suppress the antibody response of allegeneic peripheral blood mononuclear cells. In contrast, the E+/UCHT1- population, which has no other markers characteristic of T cells, fails to respond to mitogens or to provide help or suppression for an antibody response. These cells, however, are highly active natural killers. They possess Fc gamma receptors and have a characteristic staining pattern of nonspecific esterase enzyme activity. It is concluded that not all cells capable of forming E rosettes are thymus-processed cells and that this heterogeneity can be revealed by staining with the monoclonal anti-T cell reagent UCHT1.